Novel Genetic Variants in Carboxylesterase 1 Predict Severe Early‐Onset Capecitabine‐Related Toxicity. Issue 5 (30th May 2017) - Hamzic, S; Kummer, D; Milesi, S; Mueller, D; Joerger, M; Aebi, S; Amstutz, U; Largiader, CR
Abstract : An important concern with the anticancer drug capecitabine (Cp), an oral prodrug of 5‐fluorouracil, are dose‐limiting adverse effects, in particular hand‐foot syndrome (HFS) and diarrhea. Here we evaluated the association of genetic variability in all enzymes of the Cp‐activation pathway to 5‐fluorouracil with Cp‐related early‐onset toxicity in 144 patients receiving Cp. We identified a haplotype encompassing five variants in the carboxylesterase 1 ( CES1 ) gene region including an expression quantitative trait locus associated with early‐onset Cp‐toxicity (Haplotype A3: ORadditive = 2.2, 95% CI 1.2–4.0, Padjusted = 0.012; ORrecessive = 10.3, 95% CI 2.1–49.4, Padjusted = 0.0038). Furthermore, the association of two linked cytidine deaminase ( CDA) promoter variants (c.1‐451C>T: ORdominant = 4.3, 95% CI 1.3–14.2, Padjusted = 0.017; and c.1‐92A>G: ORdominant = 4.4, 95% CI 1.3–14.5, Padjusted = 0.015) with Cp‐related diarrhea was replicated. This first study identifying an association of genetic variation in CES1 with Cp‐related toxicity provides further evidence for the existence of a functional noncoding CES1 ‐variant with a possible regulatory impact.